Amylases: Biofilm Inducer or Biofilm Inhibitor? - Lahiri, Dibyajit; Nag, Moupriya; Banerjee, Ritwik; Mukherjee, Dipro; Garai, Sayantani; Sarkar, Tanmay; Dey, Ankita; Sheikh, Hassan I.; Pathak, Sushil Kumar; Edinur, Hisham Atan; Pati, Siddhartha; Ray, Rina Rani (Frontiers in Cellular and Infection Microbiology, 2021)
Biofilm is a syntrophic association of sessile groups of microbial cells that adhere to biotic and abiotic surfaces with the help of pili and extracellular polymeric substances (EPS). EPSs also prevent penetration of antimicrobials/antibiotics into the sessile groups of cells. Hence, methods and agents to avoid or remove biofilms are urgently needed. Enzymes play important roles in the removal of biofilm in natural environments and may be promising agents for this purpose. As the major component of the EPS is polysaccharide, amylase has inhibited EPS by preventing the adherence of the microbial cells, thus making amylase a suitable antimicrobial agent. On the other hand, salivary amylase binds to amylase-binding protein of plaque-forming Streptococci and initiates the formation of biofilm. This review investigates the contradictory actions and microbe-associated genes of amylases, with emphasis on their structural and functional characteristics.